2018
DOI: 10.18546/lre.16.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-markets, school diversity and social selection: Analysing the case of free schools in England, five years on

Abstract: The opening of new state schools by non-state actors has intensified debates about social selection and inequality in quasi-markets. This article examines the case of England, where the government allows anyone to apply to open a new 'free school', arguing this will improve social equity. Using data from the National Pupil Database for all 325 free schools established between 2011/12 and 2015/16, we analyse whether the students attending free schools are representative of their local neighbourhoods. We develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Darlington, Barrow-in-Furness). There is a certain irony to free school and academy conversions here, as removing fees is likely to reinforce the local polarization of school populations as more affluent students move into the newly fee-free schools, an outcome partially corroborated by Allen and Higham (2018) as well as in a new report (Private Schools Policy Reform, Forthcoming). Secondly there is a regional bias to these conversions which suggests geographies of class are almost inevitably involved.…”
Section: Resultsmentioning
confidence: 90%
“…Darlington, Barrow-in-Furness). There is a certain irony to free school and academy conversions here, as removing fees is likely to reinforce the local polarization of school populations as more affluent students move into the newly fee-free schools, an outcome partially corroborated by Allen and Higham (2018) as well as in a new report (Private Schools Policy Reform, Forthcoming). Secondly there is a regional bias to these conversions which suggests geographies of class are almost inevitably involved.…”
Section: Resultsmentioning
confidence: 90%
“…A 2018 analysis of the impacts of free schools and academies in relation to inequalities found that free schools are located in areas that are more deprived than average but have intakes that are more affluent than the average for the neighbourhoods from which they recruit, with the exception of academy chains. The authors concluded that free schools are socially selective and reproduce socioeconomic inequalities (113) (114).…”
Section: Free Schools and Academiesmentioning
confidence: 99%
“…The results of the act did not match the political expectations. One leading idea of the act was that groups in disadvantaged areas would establish new schools, but the process ultimately helped advantaged actors (Higham, 2014), and after 5 years of operation the free schools enabled by the act are selective and reproduce inequalities (Allen & Higham, 2018). Instead of systematic research, using Head's (2008) categories, the evidence seemed to be political judgement and partly practice.…”
Section: What Is the Main Issue That The Paper Addresses?mentioning
confidence: 99%